Determinants of Utilization and Cost of VHA Care by OEF/OIF Veterans Screened for Mild Traumatic Brain Injury. Issue 9 (1st September 2014) - Amara, Jomana; Pogoda, Terri K.; Krengel, Maxine; Iverson, Katherine M.; Baker, Errol; Hendricks, Ann
ABSTRACT: Objective: To determine the demographic and service characteristics that differentially impact utilization and cost of Veterans Health Administration (VHA) services for Operation Enduring Freedom and Operation Iraq Freedom (OEF/OIF) Veterans screened or evaluated for traumatic brain injury (TBI). Setting: We examined Department of Defense (DoD) and VHA administrative records of OEF/OIF Veterans who were screened or evaluated for TBI. Participants: Our study population was OEF/OIF Veterans who separated from DoD in Fiscal Years 2003–2009 and who were screened or evaluated in VHA for TBI between October 2008 and July 2009. Design: We describe the demographics and service characteristics of separated Veterans and those who accessed the VHA. We report the cost of VHA utilization and estimate a probit regression model to assess determinants of VHA utilization and costs by OEF/OIF Veterans screened and evaluated for TBI by VHA. Results: Females and Veterans older than 37 years utilize VHA services more intensely. Across all services, the Reserve Components utilize health services more than the Active Components placing more demand on VHA for services. Conclusion: VHA utilization and costs is impacted by the demographic and service characteristics of Veterans. The variation in Veteran groups incurring higher costs and utilization indicates different usage patterns of VHA services by each group with implications for patient load as the DoD deploys higher numbers of females and the Reserve Components.